Learning from women veterans who navigate invisible injuries, caregiving, and reintegration challenges - Nicholas A. Rattray; Diana Natividad; Katrina Spontak; Marina Kukla; Ai-Nghia L. Do; Leah Danson; Richard M. Frankel; Gala True (BMC, 2023)
Abstract Background As women comprise a greater proportion of military service members, there is growing recognition of how their experiences in the early phase of military to civilian transitions have an important influence on their health and reintegration outcomes. Qualitative accounts of women veterans can inform programs that support transitioning service members. Objectives We examined narratives of civilian reintegration among women veterans to understand their experiences of adjusting to community life while coping with mental health challenges. Methods/Participants We interviewed 16 post-911 era women who were within 5 years of separating from military service and developed a case study based on three participants. Main approach Interviews were audio-recorded and transcribed verbatim. Inductive thematic analysis was conducted to establish categories about reintegration. Immersion/crystallization techniques were used to identify exemplary cases that illustrated salient themes. Key results Women veterans identified establishing a future career direction, drawing on social support, and navigating health care services as major factors influencing how they adjusted to civilian life. In addition, participants also highlighted the navigation of complex and intersecting identities (i.e., wife, mother, employee, friend, veteran, patient, etc.), further magnified by gender inequalities. These women performed emotional labor, which is often rendered invisible and oriented toward their family and loved ones, while simultaneously monitoring self-care activities. During the early period of reintegration, they described how they felt marginalized in terms of accessing healthcare compared to their military spouses and male veteran peers. Conclusions Our case study suggests that there are key gaps in addressing healthcare and readjustment needs for women servicemembers, a high priority VA group, as they transition into post-military life. It is important to consider innovative ways to address specific needs of women in veteran-focused policies and programs.